2002
DOI: 10.1902/jop.2002.73.9.1043
|View full text |Cite
|
Sign up to set email alerts
|

Histocompatible Healing of Periodontal Defects After Application of an Injectable Calcium Phosphate Bone Cement. A Preliminary Study in Dogs

Abstract: Although there were no statistically significant differences between the 2 treatment groups, histological observation indicated that CPC seemed to act as a scaffold for bone formation and provided histocompatible healing of periodontal tissues in this study. This cement might be applicable to periodontal therapy; however, further investigations are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 38 publications
3
48
1
1
Order By: Relevance
“…A rheological test would solve these problems. Investigation of rheological properties could directly depict the hydration process in situ before setting of the cement, and investigate the flow characteristics and the injectable properties of CPC slurry, which is important to the use of CPC as a root canal sealer-filler [12] or as injectable biomaterials [13][14][15][16][17] for bone replacement, especially in percutaneous vertebroplasty [18][19][20] or kyphoplasty [21][22][23]. The references obtained showed that most of them focused on the improvement of injectability of the CPC paste by reducing the viscosity of the system by various methods [29][30][31], just Baroud [33] investigated the steady rheological properties of concentrated b-TCP suspension, which was non-setting system, while CPC is composed of different reactive calcium phosphates, it is a reactive concentrated suspension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A rheological test would solve these problems. Investigation of rheological properties could directly depict the hydration process in situ before setting of the cement, and investigate the flow characteristics and the injectable properties of CPC slurry, which is important to the use of CPC as a root canal sealer-filler [12] or as injectable biomaterials [13][14][15][16][17] for bone replacement, especially in percutaneous vertebroplasty [18][19][20] or kyphoplasty [21][22][23]. The references obtained showed that most of them focused on the improvement of injectability of the CPC paste by reducing the viscosity of the system by various methods [29][30][31], just Baroud [33] investigated the steady rheological properties of concentrated b-TCP suspension, which was non-setting system, while CPC is composed of different reactive calcium phosphates, it is a reactive concentrated suspension.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of high biocompatibility, easy-to-shape characteristic, and the capacity to self-setting under ambient conditions makes it an asset in the repair of hard tissue defects [2][3][4][5], and research and development on CPC have attracted much attention in recent years [5][6][7][8][9][10][11]. Based on its flow behavior before setting of slurry, CPC has been used as a root sealer-filler [12] and as an injectable biomaterial [13][14][15][16][17] for bone replacement, especially in percutaneous vertebroplasty [18][19][20] and kyphoplasty [21][22][23], which is a microtrauma surgery to treat osteoporotic vertebrae. The flow characteristics and injectability of CPC are quite important because it requires that the slurry be injectable with low resistance, no powder-liquid phase separation during the injection process, which mainly depends on a suitable rheological property of CPC slurry.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, a self-setting formulation was placed on artificially created periodontal defects but no significant difference was found between the hardened formulation and control. However, the formulation acted as a scaffold for bone formation and provided histocompatible healing of periodontal tissues [553]. Still other investigators used a self-setting formulation for direct pulp capping [554,555] and compared it to calcium hydroxide.…”
Section: Biomedical and Clinical Applicationsmentioning
confidence: 99%
“…In another study, a cement was placed on artificially created periodontal defects but no significant difference was found between the cement and control. However, the cement acted as a scaffold for bone formation and provided histocompatible healing of periodontal tissues [486]. Still other investigators used a cement for direct pulp capping [487,488] and compared it to calcium hydroxide.…”
Section: Dental Applicationsmentioning
confidence: 99%